Penerapan Strategi Learning Starts With A Quetions (LSQ) Untuk Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam Pada Kelas V SDN 179 Tanah Beru - Tika, Nursella Rastika; Dewi Hikmah Marisda; Muhammad Wajdi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The aim of this research is to determine the improvement in science learning outcomes using the Learning Start With A Question (LSQ) strategy for class V students at SDN 179 Tanah Beru. The research carried out was classroom action research (PTK). The subjects of this research were 15 class V students at SDN 179 Tanah Beru. Data collection techniques are observation, tests (evaluation), and documentation. The data obtained was then analyzed using quantitative and qualitative descriptive analysis. The results achieved quantitatively are: (1) In the first cycle, the average value of the learning outcomes of Class V students at SDN 179 Tanah Beru was obtained, namely 50. (2) In the second cycle, the average value of the learning outcomes of Class V students of SDN 179 Tanah was obtained. Beru was higher at 83.3. The science learning completion of class V students at SDN 179 Tanah Beru has also increased. In cycle I, 6 (40%) students achieved learning completeness, while in cycle II 15 (100%) students achieved learning completeness and classical learning completion was achieved. This means that learning completeness in cycle II was achieved classically because the number of students who completed it reached 80%. It can be concluded that science learning outcomes for class V students at SDN 179 Tanah Beru can be improved through the Learning Start With A Question (LSQ) strategy.